Determinants of Inappropriate Complementary Feeding Practice among 6 months-2 years old children attending Institute of Child and Mother Health (ICMH), Dhaka (The Journal of Ad-din Women's Medical College, 2023)
Background: Nutritional status of infants and young children chiefly depends on proper feeding practice; despite child rearing that often vary across population. Childhood malnutrition remains one of the major underlying causes of morbidity and mortality among younger children particularly from lower and mid income countries (LMIC) like Bangladesh.Objective: To identify determinants of practicing inappropriate complementary feeding (CF) among the infants and young children and to find out if these CF-determinants are associated with socio-demographic characteristics of child‟s families.Methods: This cross-sectionally designed study hybrid with some analytical methods were conducted among 6-24 months old children attending the out-patient and indoor departments of Pediatric, Institute of Child and Mother Health (ICMH).Results: Of total 273 children, only 20% received CF appropriately but 80% got it „inappropriately‟ based on all parameters studied, on an average. Good CF practice were significantly associated with child‟s age group (P0.95), its amount (p>0.28), feeding technique (p>0.72) and mother‟s motivation for child‟s self-feeding (p>0.27) were not significantly associated with CF practices. Most common reason for delayed CF was „tried but failed‟ in 53% and „did not know‟ the reason exactly in 10.5%. However, 10.5% mother‟s felt that breast milk was enough for the child to feed, early starting of CF being mothers‟ insuflcient breast milk in 63% and the rest 24% were ignorant on earlier starting the CF.Conclusions: Major findings of this study revealed that factors like, gender, paternal education, monthly family income, citrus food significantly differed between appropriate and inappropriate CF practices. However we strongly recommend further muti-center studies involving larger sample size before refuting or accepting our findings that this study yielded based in one hospital set up only.The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 21-27